The 4C5 cell-impermeable anti-HSP90 antibody with anti-cancer activity, is composed of a single light chain dimer. - Katerina Sidera; Avraam El Hamidieh; Avgi Mamalaki; Evangelia Patsavoudi (PLoS ONE, 2011)
MAb 4C5 is a cell impermeable, anti-HSP90 murine monoclonal antibody, originally produced using hybridoma technology. We have previously shown that mAb 4C5 specifically recognizes both the α- and to a lesser extent the β-isoform of HSP90. Additionally, in vitro and in vivo studies revealed that by selectively inhibiting the function of cell-surface HSP90, mAb 4C5 significantly impairs cancer cell invasion and metastasis. Here we describe the reconstitution of mAb 4C5 into a mouse-human chimera. More importantly we report that mAb 4C5 and consequently its chimeric counterpart are completely devoid of heavy chain and consist only of a functional kappa light chain dimer. The chimeric antibody is shown to retain the original antibody's specificity and functional properties. Thus it is capable of inhibiting the function of surface HSP90, leading to reduced cancer cell invasion in vitro. Finally, we present in vivo evidence showing that the chimeric 4C5 significantly inhibits the metastatic deposit formation of MDA-MB-453 cells into the lungs of SCID mice. These data suggest that a chimeric kappa light chain antibody could be potentially used as an anti-cancer agent, thereby introducing a novel type of antibody fragment, with reduced possible adverse immunogenic effects, into cancer therapeutics.